On the State of The Social Security System in Greece in 2020 And Projections of The Strength of The Merged Social Security Funds After the Economic and The Health Crisis of Coronavirus - Christos C. FRANGOS; Konstantinos C.FRANGOS; Panagiotis PLAKUDAKIS; Panagiotis EVANGELOPOULOS (Communications of International Proceedings, 2020)
In this paper we review the state of the Social Security system in Greece in September 2020, after the economic crisis and during the health crisis of coronavirus. A. The major reforms to the Social Insurance System were initiated by the Laws 4387/2016 and 4670/2020.The above Laws are important and need to be analyzed because International assignees, their assignment program managers and their international tax service providers need to take note of these important changes, which will impact the administration of social security in Greece. B. More specifically, the new rates and thresholds may raise international assignment costs as a greater number of employees are now part of the Social Security “net” and employees and employers may be subject to higher contribution rates. C. We present the functions of the Unified Social Security Fund, named “E.F.K.A.” and the Unified Supplementary Insurance and One-Off Benefits Fund, named “E.T.E.A.E.P.”    D.  Furthermore, we compare the countries which belong to the Organization for Economic Cooperation and Development (OECD) with respect to two important and internationally recognized measures for the depth and intensity of Social Policy. The measures which we use are the following: Net Pension Replacement Rate (NPRR) and Gross Pension Wealth (GPW).
Keywords: Social Security System; Greece; Coronavirus